Globalisation of the automotive industry: main features and trends. (12th December 2008) - Sturgeon, Timothy J.; Memedovic, Olga; Van Biesebroeck, Johannes; Gereffi, Gary
This paper lays out the main features of the global automotive industry and identifies several important trends. A boom in developing country sales and production has not yet overshadowed the importance of existing markets in developed regions. Regional integration is very strong at an operational level, yet the industry has recently developed a set of global-scale value chain linkages, and retains national and local elements as well. The paper highlights how global, regional, national and local value chains are nested to create a pattern of global integration that is distinctive to the industry. We use global value chain analysis to help explain the limits of build-to-order in the industry, the role of regional and global suppliers, the shifting geography of production and how the characteristics of value chain linkages in the industry favour tight integration and regional production. We describe how industry concentration focuses power in the hands of a few large lead firms and discuss the implications of this for value chain governance and the geography of production.